Early γGT and bilirubin levels as biomarkers for regeneration and outcomes in damaged bile ducts after liver transplantation. Issue 3 (3rd January 2023) - Junger, Henrik; Mühlbauer, Marco; Brennfleck, Frank W.; Schurr, Leonhard A.; Goetz, Markus; Eggenhofer, Elke; Kirchner, Gabriele; Evert, Katja; Fichtner‐Feigl, Stefan; Geissler, Edward K.; Schlitt, Hans J.; Brunner, Stefan M.
Abstract: Background: Early patient and allograft survival after liver transplantation (LT) depend primarily on parenchymal function, but long‐term allograft success relies often on biliary‐tree function. We examined parameters related to cholangiocyte damage that predict poor long‐term LT outcomes after donation after brain death (DBD). Methods: Sixty bile ducts (BD) were assessed by a BD damage‐score and divided into groups with "major" BD‐damage ( n  = 33) and "no relevant" damage ( n  = 27) during static cold storage. Patients with "major" BD damage were further investigated by measuring biliary excretion parameters in the first 14 days post‐LT (followed‐up for 60‐months). Results: Patients who received LT showing "major" BD damage had significantly worse long‐term patient survival, versus grafts with "no relevant" damage ( p  = .03). When "major" BD damage developed, low bilirubin levels ( p  = .012) and high gamma‐glutamyl transferase (GGT)/bilirubin ratio ( p  = .0003) were evident in the early post‐LT phase (7–14 days) in patients who survived (> 60 months), compared to those who did not. "High risk" patients with bile duct damage and low GGT/bilirubin ratio had significantly shorter overall survival ( p  < .0001). Conclusions: Once "major" BD damage occurs, a high GGT/bilirubin ratio in the early post‐operative phase is likely indicator of liver and cholangiocyte regeneration, and thus a harbinger of good overall outcomes. "Major" BD damage without markers of regeneration identifies LT patients that could benefit from future repair therapies.